2004
DOI: 10.1128/iai.72.2.1096-1106.2003
|View full text |Cite
|
Sign up to set email alerts
|

Conservation ofBabesia bovisSmall Heat Shock Protein (Hsp20) among Strains and Definition of T Helper Cell Epitopes Recognized by Cattle with Diverse Major Histocompatibility Complex Class II Haplotypes

Abstract: Babesia bovis small heat shock protein (Hsp20) is recognized by CD4؉ T lymphocytes from cattle that have recovered from infection and are immune to challenge. This candidate vaccine antigen is related to a protective antigen of Toxoplasma gondii, Hsp30/bag1, and both are members of the ␣-crystallin family of proteins that can serve as molecular chaperones. In the present study, immunofluorescence microscopy determined that Hsp20 is expressed intracellularly in all merozoites. Importantly, Hsp20 is also express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 60 publications
3
22
0
Order By: Relevance
“…This fact is supported by observation of Norimine et al [55] who studied the protective power of Babesia bovis HSP20 as a candidate vaccine [55]. They claimed that "the most immunostimulatory region of B. bovis Hsp20 for T helper cells from the cattle used in this study is the Nterminal region spanning amino acid 11 to 62".…”
Section: Discussionsupporting
confidence: 62%
“…This fact is supported by observation of Norimine et al [55] who studied the protective power of Babesia bovis HSP20 as a candidate vaccine [55]. They claimed that "the most immunostimulatory region of B. bovis Hsp20 for T helper cells from the cattle used in this study is the Nterminal region spanning amino acid 11 to 62".…”
Section: Discussionsupporting
confidence: 62%
“…6). This is supported by recent publications showing that DQ molecules in cattle are relevant for peptide presentation to T helper cells in immune responses against FMDV-derived peptides (15), Babesia bovis (26), and Anaplasma marginale (6). Furthermore, FIG.…”
Section: Vol 83 2009 Anchor Residues Of Bovine Fmdv T-cell Epitopessupporting
confidence: 58%
“…In cattle, the MSP2-specific antibody response is predominantly directed toward the hypervariable region rather than the flanking conserved regions [86, 87]. This is not surprising, as the hypervariable region is predicted to be surface exposed [86] and antigenic variation is detected under conditions of immune pressure and selection, which would not apply to surface exposed conserved sequences. Evasion of the anti-MSP2 antibody response by newly emerging variants during persistent infection was documented for A. marginale [49] and for A. phagocytophilum in sheep [7, 88].…”
Section: Subversion and Dysregulation Of The Immune Responsementioning
confidence: 99%
“…As new antigenic variants of MSP2 or MSP3 arise during persistent infection, T cells may be continually primed to these new variants, which are then suppressed or deleted as antigen load increases. We have shown that both hypervariable as well as conserved regions of MSP2 contain CD4 + T cell epitopes [86, 90]. During persistent infection, there may also be continuous priming and expansion of CD4 + T cells to epitopes on subdominant outer membrane proteins [61].…”
Section: Subversion and Dysregulation Of The Immune Responsementioning
confidence: 99%